Operation and Maintenance of Water Structures and Their Accessories - عيسى, لونا (Latakia University Journal -Engineering Sciences Series, 2020)
Maintenance in water structures is defined as a specific pre-planned execution, carried out at the specified time, which leads to the permanence of these water structures, and their continued functioning with economic and effective benefits. Water structures of various types and during normal use require care and maintenance in the required form, and at the appropriate times, to have a permanent readiness, and to maintain the correct state, in addition to prolonging their life. Therefore, periodic maintenance of the water structures is of great importance due to its economic implications. The aim of this research is to highlight the importance of regular and integrated maintenance of water structures, to achieve optimum economic investment, and to study the possibility of applying maintenance works to the faults of various water structures. It also displays different types of maintenance and their applicability to these structures. Finally, it provides an overview of the guidelines and recommendations for the safety of these water structures, and the safety of personnel working in this engineering field.